2014
DOI: 10.5194/acp-14-3151-2014
|View full text |Cite
|
Sign up to set email alerts
|

The 2013 severe haze over southern Hebei, China: model evaluation, source apportionment, and policy implications

Abstract: Abstract. Extremely severe and persistent haze occurred in January 2013 over eastern and northern China. The record-breaking high concentrations of fine particulate matter (PM 2.5 ) of more than 700 µg m −3 on hourly average and the persistence of the episodes have raised widespread, considerable public concerns. During that period, 7 of the top 10 polluted cities in China were within the Hebei Province. The three cities in southern Hebei (Shijiazhuang, Xingtai, and Handan) have been listed as the top three po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
159
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 328 publications
(175 citation statements)
references
References 54 publications
(62 reference statements)
12
159
1
Order By: Relevance
“…A number of studies apply nested simulations with a horizontal resolution in the innermost domain of 12 km (30) or 9 km (31). Wang et al (30) compared domainwide PM 2.5 predictions at 36-km and 12-km grid resolutions, and found that the use of a finer grid changed PM 2.5 performance from a slight underprediction to a moderate overprediction. In our study, the 36-km resolution achieved better model performance than the 12-km resolution.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies apply nested simulations with a horizontal resolution in the innermost domain of 12 km (30) or 9 km (31). Wang et al (30) compared domainwide PM 2.5 predictions at 36-km and 12-km grid resolutions, and found that the use of a finer grid changed PM 2.5 performance from a slight underprediction to a moderate overprediction. In our study, the 36-km resolution achieved better model performance than the 12-km resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Trajectory cluster 5 mainly originated from Ningxia Province and passed over Shaanxi, Shanxi, and Hebei before arriving at Shijiazhuang, accounting for 10.8 % of the total trajectories, showing the features of small-scale, short-distance air mass transport and significantly elevated levels of PM 10 (451 µg m −3 ), PM 2.5 (303 µg m −3 ), SO 2 (83 µg m −3 ), NO 2 (104 µg m −3 ), and CO (4.8 mg m −3 ) with trajectory cluster 5 possibly associated with the sources and accumulation of pollutants from surrounding areas. As it is well known that the Beijing-Tianjin-Hebei region is one of the most severely polluted areas in China (Gu et al, 2011;Zhao et al, 2012;Chen et al, 2013;Bi et al, 2014;Wang et al, 2014), it might be an important reason why the concentrations of atmospheric pollutants were higher with trajectory clusters 1 and 5 (Fig. 11 and Table 2).…”
Section: Backward Trajectory and Pscf Analysismentioning
confidence: 99%
“…Looking at interannual variability, for example in 2013, the fertilization peaks of March, July and October are clearly observed . It is interesting to note that the highest January surface concentration (5.1 µg m −3 ) and satellite total column (7.8 ×10 15 molec cm −2 ) are measured during the severe winter pollution episode of 2013 (see Boynard et al, 2014;Wang et al, 2014). The correlation analysis for the monthly values of the 43 NNDMN sites gives a Pearson's r equal to 0.39 (considering the IASI data with a monthly relative retrieval error below 100 %) and a slope of the regression equal to 0.21 (n = 1149).…”
Section: Regional Focusmentioning
confidence: 99%